Predicting the effects of urbanization on runoff after frequent rainfall events. Issue 1 (4th March 2018) - Ohana-Levi, Noa; Givati, Amir; Alfasi, Nurit; Peeters, Aviva; Karnieli, Arnon
ABSTRACT: Urbanization dynamics are commonly subjected to powerful market forces, only partly managed by land-use plans. The density, location and pattern of urbanized areas affect rainfall-runoff relations. Consequently, it is essential to understand future impacts of urbanization on runoff and produce focused regulation. The goal was to analyze land-cover scenarios and their impact on runoff in an urbanized watershed in Israel. Present and predicted land-cover scenarios in a densely populated watershed were produced. The runoff response to rainfall was then simulated using a hydrological model. The impact of implementing afforestation and quarrying national outline plans was considered. By the year 2050, 50% of the watershed will be urbanized with a linear increase in runoff response. Afforestation and quarrying plans show little effect on runoff, although quarries may decrease runoff through percolation. As urbanization is expected to continue spreading in adjacent watersheds, statutory measures should be applied to mitigating runoff.